2015
DOI: 10.1128/aem.00096-15
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Enterococcus faecalis Biofilms with Phage Therapy

Abstract: Phage therapy has been proven to be more effective, in some cases, than conventional antibiotics, especially regarding multidrug-resistant biofilm infections. The objective here was to isolate an anti-Enterococcus faecalis bacteriophage and to evaluate its efficacy against planktonic and biofilm cultures. E. faecalis is an important pathogen found in many infections, including endocarditis and persistent infections associated with root canal treatment failure. The difficulty in E. faecalis treatment has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
180
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(186 citation statements)
references
References 53 publications
1
180
0
5
Order By: Relevance
“…High host specificity, bacterial susceptibility and potential for bioengineering for even more refined targeting and resilience to acquired resistance make phages particularly promising antimicrobials in contexts where antibiotics are ineffective or inappropriate [1,29]. Phage research offers promise for advancements both in historical applications of medical phage therapy against infection [13,19] and novel applications throughout biotechnology and agriculture [3,5,10].…”
Section: Introductionmentioning
confidence: 99%
“…High host specificity, bacterial susceptibility and potential for bioengineering for even more refined targeting and resilience to acquired resistance make phages particularly promising antimicrobials in contexts where antibiotics are ineffective or inappropriate [1,29]. Phage research offers promise for advancements both in historical applications of medical phage therapy against infection [13,19] and novel applications throughout biotechnology and agriculture [3,5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm-associated VRE infections are challenging for treatment. EFDG1, isolated from sewage water, was efficient not only in nearly eliminating 2-week old E. faecalis biofilms of around 100 μm thickness but also in prevention of E. faecalis root canal infection [52,56].…”
Section: Phage Therapy Against Vrementioning
confidence: 99%
“…Two lytic phages were recently described that were found to reduce Staphylococcal biofilms by 2 logs and the frequency of bacteriophage resistance developing in the bacteria was sufficiently low to merit these bacteriophages as potential candidates for therapy (42). Another recent study found a bacteriophage, EFDG1, to have effective lytic activity against planktonic and biofilm cultures of Enterococcus faecalis and E. faecium isolates, regardless of their antibiotic resistance profile (43). In addition, EFDG1 efficiently prevented an ex vivo E. faecalis root canal infection (43).…”
Section: Bacteriophage Therapy To Fight Biofilm Infectionsmentioning
confidence: 99%
“…Another recent study found a bacteriophage, EFDG1, to have effective lytic activity against planktonic and biofilm cultures of Enterococcus faecalis and E. faecium isolates, regardless of their antibiotic resistance profile (43). In addition, EFDG1 efficiently prevented an ex vivo E. faecalis root canal infection (43). There are a number of advantages in using bacteriophages to treat biofilm-related infections.…”
Section: Bacteriophage Therapy To Fight Biofilm Infectionsmentioning
confidence: 99%